Use of Proton Pump Inhibitors in Hungary: Mixed-Method Study to Reveal Scale and Characteristics - Matuz, Mária; Benkő, Ria; Engi, Zsófia; Schváb, Krisztina; Doró, Péter; Viola, Réka; Szabó, Mária; Soós, Gyöngyvér (Frontiers in Pharmacology, 2020)
Background: Due to their efficacy and tolerability, utilization of proton pump inhibitors (PPI) has significantly increased worldwide. Parallel to the clinical benefits, potential long-term side effects have been observed, which, along with increasing medical expenses and potential drug interactions, justifies the analysis of the trends of utilization. Objective: The aim of the present study was to show the level, pattern and characteristics of PPI use. Methods: We assessed the nationwide use of proton pump inhibitors in ambulatory care based on aggregated utilization data from the National Health Insurance database. The annual PPI utilization was expressed as the number of packages and as number of DDDs per 1000 inhabitants and per year. For 2018, we estimated PPI exposure as the number of packages and as the number of DDDs per user per year. The annual reimbursement costs of proton pump inhibitors were also calculated. Moreover, three patient-level surveys were carried out in non-gastroenterological inpatient hospital departments to reveal characteristics of proton pump inhibitor use, namely dose, duration and indication. Results: The PPI utilisation increased from 5867.8 thousand to 7124.9 thousand packages and from 41.9 to 50.4 DDD per 1000 inhabitants and per day between 2014 and 2018. Nationwide data showed that 14 % of the adult population was exposed to proton pump inhibitors in 2018, while among hospitalized patients, the prevalence of proton pump inhibitor use was between 44.5% and 54.1%. Pantoprazole was the most frequently used active ingredient, both in the nationwide data and in the patient-level surveys. In the patient-level survey in majority of patients (71.5%–80.0%) PPIs were prescribed for prophylaxis. Many inpatients (29.4%–36.9%) used 80 mg pantoprazole per day. The average number of PPI packages per user was 6.5 in 2018 in the nationwide data. The duration of PPI therapy was typically between 1 and 5 years in the patient-level surveys and nearly 20% of the inpatients had been taking proton pump inhibitors for more than 5 years. Conclusions: Our data suggests that Hungarian patients receive proton pump inhibitors in high doses and for a long time. Use of PPIs beyond their recommended indications was also found.